A Case Study on the Impact of Boundary Layer Turbulence on Convective Clouds in the Eastern Margin of the Tibetan Plateau - Ting Wang; Maoshan Li; Yonghao Jiang; Yuchen Liu; Ming Gong; Shaoyang Wang; Peng Sun; Yaoming Ma; Fanglin Sun (Remote Sensing)
In this study, we utilized ECMWF Reanalysis of the Global Climate at Atmospheric Resolution 5 (ERA5) data, FengYun-4B satellite (FY-4B) data, a Wind3D 6000 Three-Dimensional Scanning Laser Wind Radar, and raindrop spectrum data to analyze the circulation background, convective cloud changes, boundary layer wind field variations, and precipitation drop size spectrum characteristics of a severe convective rainfall process that occurred on 3 April 2024 in the eastern margin of the Tibetan Plateau. The findings indicated the following: (1) The rain belt of this precipitation event showed a southwest–northeast trend. During the vigorous development of convection, the rainfall intensity and total precipitation at the station increased, with a wider raindrop spectrum, and the raindrop spectrum of this precipitation process was unimodal. (2) On 3 April, the interaction between the eastward movement of the plateau trough at 500 hPa and the upper-level jet stream at 200 hPa in the eastern Tibetan Plateau and the Sichuan Basin area, along with the necessary conditions for precipitation, such as energy and moisture, led to severe convective rainfall. (3) This intense convective precipitation process was caused by the vigorous convective clouds that developed in the eastern part of the Tibetan Plateau. As these clouds developed and moved eastward out of the plateau, they precipitated with increased turbulence intensity at the station, leading to the generation of intense convective activities at the site. (4) One hour before the precipitation, there were significant increases in horizontal wind speed, vertical air velocity, and turbulence intensity within the boundary layer, and there were also significant changes in the horizontal wind direction. The results obtained can provide important theoretical references for the prediction of severe convective rainfall and the performance of numerical simulations thereon.